Restoring mitochondrial DNA copy number preserves mitochondrial function and delays vascular aging in mice. Issue 4 (9th May 2018) - Foote, Kirsty; Reinhold, Johannes; Yu, Emma P. K.; Figg, Nichola L.; Finigan, Alison; Murphy, Michael P.; Bennett, Martin R.
Summary: Aging is the largest risk factor for cardiovascular disease, yet the molecular mechanisms underlying vascular aging remain unclear. Mitochondrial DNA (mtDNA) damage is linked to aging, but whether mtDNA damage or mitochondrial dysfunction is present and directly promotes vascular aging is unknown. Furthermore, mechanistic studies in mice are severely hampered by long study times and lack of sensitive, repeatable and reproducible parameters of arterial aging at standardized early time points. We examined the time course of multiple invasive and noninvasive arterial physiological parameters and structural changes of arterial aging in mice, how aging affects vessel mitochondrial function, and the effects of gain or loss of mitochondrial function on vascular aging. Vascular aging was first detected by 44 weeks (wk) of age, with reduced carotid compliance and distensibility, increased β‐stiffness index and increased aortic pulse wave velocity (PWV). Aortic collagen content and elastin breaks also increased at 44 wk. Arterial mtDNA copy number (mtCN) and the mtCN‐regulatory proteins TFAM, PGC1α and Twinkle were reduced by 44 wk, associated with reduced mitochondrial respiration. Overexpression of the mitochondrial helicase Twinkle (Tw + ) increased mtCN and improved mitochondrial respiration in arteries, and delayed physiological and structural aging in all parameters studied. Conversely, mice with defective mitochondrial polymerase‐gamma (PolG) and reduced mtDNA integrity demonstrated accelerated vascular aging. Our study identifies multiple early and reproducible parameters for assessing vascular aging in mice. Arterial mitochondrial respiration reduces markedly with age, and reduced mtDNA integrity and mitochondrial function directly promote vascular aging.